Impact of self-financing on the overall funding of public hospitals in Kisangani, Democratic Republic of the Congo: Challenges and prospects - Yanyongo, Bijou Folo; Nswele, Odon Ilundu; Mukandu, Leyka Basua Babintu; Boumo, Benoit An’tiokondi; Assani, Raymond Ramazani; Mawunu, Monizi; Koto-Te-Nyiwa Ngbolua, Jean-Paul (Orapuh Journal, 2025)
Introduction Financing public hospitals in the Democratic Republic of the Congo, especially in Kisangani (Tshopo Province), remains a major challenge for the provision of quality health services. Although several funding sources exist, the specific contribution of self-financing to hospital budgets has not been well documented, leaving its role in financial sustainability unclear. Purpose This study evaluated the role of self-financing in the overall funding of the General Reference Hospitals of Makiso, Lubunga, and Tshopo between 2020 and 2022. Methods A quantitative research design was adopted, using an inductive and accounting approach. Nine annual financial reports (three per hospital) for the period 2020–2022 were analysed. The general trend analysis technique and Pearson’s linear correlation were used to determine the relationship between self-financing and total hospital funding. Results On average, self-financing accounted for 62.6% of total hospital funding. A strong positive correlation was found between self-financing and total funding (r = 0.95), indicating that self-financing significantly influenced the financial performance of the hospitals during the study period. Conclusion Although self-financing contributes substantially to hospital budgets, it does not guarantee financial autonomy, as public hospitals remain heavily dependent on households. This dependence places a financial burden on families and encourages overbilling. To address this, it is recommended that the government and its technical and financial partners diversify and strengthen funding mechanisms to reduce reliance on households and ensure more affordable and equitable hospital services in Kisangani. This study is one of the first empirical assessments of self-financing in Congolese public hospitals, quantifying its share in overall financing and outlining its implications for the sustainability of the health system.